2008
DOI: 10.1111/j.1365-294x.2008.03771.x
|View full text |Cite
|
Sign up to set email alerts
|

Landscape genetics and hierarchical genetic structure in Atlantic salmon: the interaction of gene flow and local adaptation

Abstract: Disentangling evolutionary forces that may interact to determine the patterns of genetic differentiation within and among wild populations is a major challenge in evolutionary biology. The objective of this study was to assess the genetic structure and the potential influence of several ecological variables on the extent of genetic differentiation at multiple spatial scales in a widely distributed species, the Atlantic salmon, Salmo salar. A total of 2775 anadromous fish were sampled from 51 rivers along the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
250
0
23

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(283 citation statements)
references
References 82 publications
10
250
0
23
Order By: Relevance
“…Along with other studies, the results illustrate that the dynamics of local adaptation cannot be understood solely at the level of individual populations, but integrate geographical distance, spatially varying environmental conditions and demographic parameters such as gene flow (Adkison, 1995;Hansen et al, 2002;Dionne et al, 2008;Fraser et al, 2011). Our findings also suggest that diversifying selection between hatchery and wild salmonids may involve different loci than those under selection between wild populations.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Along with other studies, the results illustrate that the dynamics of local adaptation cannot be understood solely at the level of individual populations, but integrate geographical distance, spatially varying environmental conditions and demographic parameters such as gene flow (Adkison, 1995;Hansen et al, 2002;Dionne et al, 2008;Fraser et al, 2011). Our findings also suggest that diversifying selection between hatchery and wild salmonids may involve different loci than those under selection between wild populations.…”
Section: Discussionmentioning
confidence: 53%
“…Similar conclusions have been reached for Pacific salmonids assuming realistic demographic parameters (Adkison, 1995), although it should be noted that Vähä et al (2008) used the same approach in a study of tributary populations of Atlantic salmon (Salmo salar) and concluded that local adaptation was likely to occur at smaller geographical scales within a river system. Dionne et al (2008) analyzed Atlantic salmon populations using landscape genetics methods and observed a hierarchical genetic structure that coincided with environmental variables, thereby also providing indirect evidence for local adaptation primarily occurring at the scale of regions rather than at the level of individual populations. Finally, a review of studies investigating local adaptation in salmonids at different geographical scales by directly estimating fitness showed that adaptation generally becomes more prevalent as geographical distance increases (Fraser et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, other less obvious ecological factors, for instance those linked to the presence of unsuitable natural habitat, might also influence neutral genetic structure if such factors limit gene flow (McRae and Beier, 2007) or induce genetic drift through a reduction in population size (Hoffmann and Willi, 2008). The effects of ecological factors (for example, variation in temperature, habitat fragmentation and local environment) or contaminants (for example, heavy metals) on neutral genetic structure have been described previously for both plants (for example, Schmidt et al, 2009) and animals (for example, Dionne et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the appropriate scale for biological conservation and management units tends to be at the level of an individual river, and large-scale genetic analysis across the species' distribution has demonstrated that this is generally true (King et al, 2001). Gene flow does occur between salmon populations, but is constrained by local adaptation at the regional scale and is influenced by both coastal distance and temperature regime (Dionne et al, 2008). Valiente et al (2010) have recently demonstrated that warm climate conditions tend to increase straying and, consequently, gene flow among salmon in southern French rivers.…”
Section: Introductionmentioning
confidence: 99%